Prescription pattern and rationality of antihypertensive drugs in patients of type 2 diabetes with hypertension: a pilot study - Bhore, A. S.; Khandare, Kalyani; Bansod, K. A. (International Journal of Research in Medical Sciences, 2019)
Background: As presence of hypertension (HTN) in type 2 diabetes significantly increases risk of morbidity and mortality, its control with rational use of antihypertensives is essential. Authors performed this study to understand the current prescribing pattern of antihypertensives in patients of type 2 diabetes and their assess the rationality to recommendations of JNC-8 guidelines. Methods: Authors performed a cross sectional survey of prescription of diagnosed patients of diabetes with HTN at a tertiary care hospital. Prescription of patients attending medicine OPD were scanned. Data was collected over 2 month and analyzed with descriptive statistics. Results: In 76 patients analysed, mean age was 54.9±9.3 years and 51.3% were females. Insulin and oral antidiabetic agents were prescribed in 16 (21.1%) and 73 (96.1%) patients respectively. One, two, three and four antihypertensive drugs were prescribed in 44 (57.9%), 28 (36.8%), 3 (3.9%) and 1 (1.3%) patients respectively and 24 (31.6%) of them were fixed dose combinations. Among antihypertensives, angiotensin converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs), thiazide diuretics, beta blockers (BBs) and calcium channel blockers (CCBs) were present in 29 (38.2%), 26 (34.2%), 22 (28.9%), 21 (27.6%) and 14 (18.4%) respectively. In individual drugs, ramipril (28.9%) was most common followed by telmisartan (26.3%), hydrochlorothiazide (26.3%), atenolol (16, 21.1%) and amlodipine (17.1%) were frequently prescribed. In adjuvant drugs, antiplatelet (52.6%) and statins (56.6%) were common. This pattern of prescription was as per the recommendations of recent JNC-8 guidelines for treatment of hypertension. Conclusions: ACEIs/ARB are the most preferred for HTN treatment in type 2 diabetes mellitus. Prescription of antihypertensives in our set up was rational as per JNC-8 recommendations.